2007
DOI: 10.1089/lap.2006.0186
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Totally Extraperitoneal Hernia Repair Versus Open Lichtenstein Hernia Repair: Results and Complications

Abstract: Whereas open Lichtenstein inguinal herniorrhaphy is generally accepted as a safe, well-understood method with a high success rate, the laparoscopic repair of a inguinal hernia is a fairly recent technique. Although the laparoscopic approach to a hernia repair procedure is associated with less pain and faster recovery than open repair, many surgeons are not familiar with this technique owing to technical demands and a long learning curve. This study compares the results and complications between open tension-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 42 publications
1
28
0
3
Order By: Relevance
“…The recurrence rates are very low after both open and laparoscopic mesh repairs, and randomized studies have not shown any signifi cant difference with regard to either adverse effects or recurrence. 10,18,19 In a TEP repair the peritoneum is not penetrated, and the trocars are placed preperitoneally in a space created between the peritoneum and the fascia. The TEP approach involves the creation of a preperitoneal space posterior to the inguinal canal either with a telescope or, more commonly, with a preperitoneal distention balloon system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The recurrence rates are very low after both open and laparoscopic mesh repairs, and randomized studies have not shown any signifi cant difference with regard to either adverse effects or recurrence. 10,18,19 In a TEP repair the peritoneum is not penetrated, and the trocars are placed preperitoneally in a space created between the peritoneum and the fascia. The TEP approach involves the creation of a preperitoneal space posterior to the inguinal canal either with a telescope or, more commonly, with a preperitoneal distention balloon system.…”
Section: Discussionmentioning
confidence: 99%
“…1,3,4,18,22 Nevertheless, the laparoscopic approach has been slow in gaining popularity among surgeons for several reasons. First, more advanced technical skills are required compared with a conventional Lichtenstein repair.…”
Section: Discussionmentioning
confidence: 99%
“…Poor familiarity with posterior perspective of the complex inguinal anatomy is an important factor for the steep learning curve for the laparoscopic inguinal hernioplasty. [4][5][6][7] A lot of confusions and misunderstandings abound regarding the retropubic space of Retzius and the subinguinal space of Bogros. [8][9][10][11][12] Space of Bogros was first described in 1823 by French anatomist Annet Jean Bogros.…”
Section: Introductionmentioning
confidence: 99%
“…In our first few cases, incision was placed in the midline a few centimeters below the umbilicus, as described for LAP-TEP. 4 Later, we placed a horizontal incision within the umbilicus. By moving the skin incision closer to the umbilicus, we created a longer channel to the extraperitoneal space, and initial CO 2 leakage problems were minimized.…”
mentioning
confidence: 99%